Exploring Thinking and Speaking Patterns of Pre-service Teachers in Microteaching: A Cognitive-Reflective Perspective - Nurrahmah, Nurrahmah; Rahman, Abdul; Annas, Suwardi (Indonesian Journal Publisher, 2025)
This study aims to explore patterns of reflective thinking in pre-service teachers’ oral communication during microteaching sessions. It employed a qualitative approach with an exploratory case study design. The participants were sixth-semester students of the Mathematics Education Study Program enrolled in a microteaching course. Data were collected through participant observation, semi-structured interviews, and video documentation of teaching practices, and analyzed using thematic analysis. The findings revealed five key patterns: (1) internal selection of main ideas prior to speaking, (2) a tendency to lose the main ideas during elaboration, (3) the significant influence of content mastery on communication structure, (4) limitations in idea development, and (5) irregularities in oral delivery. These patterns suggest that students have not fully engaged in reflective thinking processes when speaking in front of the class. The study concludes that integrating a cognitive-reflective approach into microteaching training is essential to enhance students' ability to manage ideas and construct systematic, meaningful communication. This research contributes to the development of more reflective and idea-focused learning designs for pre-service teacher education.